2017
DOI: 10.1109/jlt.2017.2676241
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Femtosecond Optical Vortex Beams in All-Fiber Mode-Locked Fiber Laser Using Mode Selective Coupler

Abstract: We experimentally demonstrated a high-order optical vortex pulsed laser based on a mode selective all-fiber fused coupler composed of a single-mode fiber (SMF) and a few-mode fiber (FMF). The fused SMF-FMF coupler inserted in the cavity not only acts as mode converter from LP01 mode to LP11 or LP21 modes with a broadband width over 100 nm, but also directly delivers femtosecond vortex pulses out of the mode locked cavity. To the best of our knowledge, this is the first report on the generation of high-order pu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
59
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(60 citation statements)
references
References 46 publications
0
59
0
1
Order By: Relevance
“…At present, vortex beams in the fiber lasers have been demonstrated because of the promising applications in the quantum optics, 188 optical micromanipulation, 189 rotation detection, 190 WDM (modedivision multiplexing) systems, 191 and nonlinear fiber optics. 192 In the fiber systems, the vortex beams are generally realized by the modulating elements, including the mode selective couplers, 193,194 long period fiber gratings, 195,196 and microstructured fiber facets. 197 The mode-locked vortex beams through the mode fibers in the all-fiber lasers have been reported.…”
Section: Rogue Waves Induced By the Optical Vortex Beams In The Fibermentioning
confidence: 99%
“…At present, vortex beams in the fiber lasers have been demonstrated because of the promising applications in the quantum optics, 188 optical micromanipulation, 189 rotation detection, 190 WDM (modedivision multiplexing) systems, 191 and nonlinear fiber optics. 192 In the fiber systems, the vortex beams are generally realized by the modulating elements, including the mode selective couplers, 193,194 long period fiber gratings, 195,196 and microstructured fiber facets. 197 The mode-locked vortex beams through the mode fibers in the all-fiber lasers have been reported.…”
Section: Rogue Waves Induced By the Optical Vortex Beams In The Fibermentioning
confidence: 99%
“…An optical circulator assures unidirectional operation. The outer ring cavity consists of the MKR (with a red ring structure in the picture), PC3, and an SMF and FMF coupler (coupling ratio 90:10), which is used to convert LP 01 mode to high-order LP 11 mode [26,27]. The output spectrum is analyzed by an optical spectrum analyzer (OSA, YOKOGAWA, AQ6370C) and the output beam profiles are recorded using a CCD camera (InGaAs camera, Model C10633-23 from Hamamatsu Photonics).…”
Section: Methodsmentioning
confidence: 99%
“…However, to the best of our knowledge, there have been few reports about a multiwavelength switchable fiber laser with vortex beams. In our prior work, a single-mode fiber (SMF) and few-mode fiber (FMF) coupler was first proposed to overcome the constraint of broadband mode conversion [26,27], which is a promising method to produce efficient femtosecond OVBs. By using a similar fiber mode coupler, cylindrical vector beams with a switchable dual-wavelength pulsed laser were also presented [28].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the combination of a few-mode fibe and a SMF, Ismaeel et al [24] demonstrated a MSC with relatively simple configuratio and fabrication process, which can excite specifi higher-order modes with high efficien y and purity. Recently, femtosecond [25] CVB pulse generation from modelocked fibe laser based on nonlinear polarization rotation effect and nanosecond [26] CVB pulse generation from mode-locked fibe laser based on nonlinear amplifie loop mirror have been reported based on the MSCs with SMF and TMF. Therefore, MSC composed of both SMF and few-mode fibe can convert the fundamental mode in SMF to the higher-order modes in few-mode fibe with high conversion efficien y and broad conversion bandwidth.…”
mentioning
confidence: 99%